Rancang Bangun Timbangan Beras Digital Menggunakan Arduino - Budiarto, Adi; Izzuddin, Ahmad; Misdiyanto, Misdiyanto (Fakultas Teknik dan Informatika Universitas Panca Marga, 2022)
Rice is a staple food that is indispensable for the people of Indonesia. Each family consumes an average of at least 2 kg of rice every day. In distribution, the rice purchased by distributors from rice producers is in the form of one sack with a weight of 25 kg. Rice weighing 25 kg can be sold to consumers. However, there are some people who cannot buy in large quantities, this factor is due to the lack of a person's economy. Therefore, the weight of rice must be adjusted into sizes of 1/2 kg, 1 kg, 2 kg and 5 kg so that rice can be sold to consumers both wholesale and retail. The rice weight conversion process generally uses the manual method, namely the rice is weighed using a traditional scale. The dosing system for selling rice still uses kilos or by using analog scales, where such a system still has drawbacks besides requiring a lot of energy and time. The manual weighing process also has a negative impact that is detrimental to consumers where traders in the market usually commit fraud in trading by modifying the weighing device, so that the weighing results are reduced and do not match the actual dose, in order to make various efforts to obtain unilateral profits, which of course this action can harm consumers. In this study, the Load Cell Sensor was used to determine how much rice was already in the weighing tank, the Servo was used to open and close the rice exit door from the storage to the weighing tank, and Arduino Uno as a microcontroller to process data from the Load Cell and control the Servo. The result of this research is the creation of a system for weighing rice with the amount specified by the user, and with the Load Cell sensor accuracy of 99.05% it can be concluded that the design of this rice serving system has achieved the expected results. Keywords : Rice Serving, Arduino Uno, Load Cell.